Study of strain localizations in a polycrystalline medium in presence of a quasi-static crack (Fracture and Structural Integrity, 2017)
Numerical techniques have been widely applied in many recent works to investigate micro-scale behavior of materials. This work focuses on the analysis of strain localizations in a Nickel-based alloy, Haynes 230. Numerical models and experiments concern the study of the strain field generated around the crack tip inside a polycrystalline medium when the crack is quasi-static (not propagating). Experimentally, the tests were conducted in load control; one face of the specimens was monitored by high-resolution Digital Image Correlation (DIC) technique to evaluate the strain field ahead of the crack tip. The simulations were conducted adopting an open source finite element code, Warp3D, which implements a state of art Crystal Plasticity (CP) model. The models of the polycrystalline matrix were created considering the data obtained inspecting the specimen surface by the Electron Back-Scatter Diffraction (EBSD) technique, which allowed defining grains size and orientations. Experimental and numerical results were then compared in terms of strain localizations to evaluate the prediction capabilities of the models. The comparison focused on strain field extension and active grains.
Keywords: Crystal Plasticity; Digital image correlation; Polycrystalline aggregate